Genetic types and provenance indication of clastic amphibole in the South Yellow Sea - Wang, Mengyao; Jin, Bingfu; Liu, Jian; Gao, Maosheng; Gao, Jianhua; Jia, Jianjun (Frontiers in Marine Science, 2024)
The main focus of studying sediment sources in marine areas is to determine the properties of detrital minerals originating from different rivers. Variations in the characteristics of detrital minerals occur due to differences in the types of source rocks within the watershed. Determining the source rock of detrital minerals in the marine area can improve the accuracy of provenance analysis. Electron probe microanalysis of 258 amphibole grains from six surface stations in the South Yellow Sea (SYS) was conducted to calculate the numerical and characteristic values of cations in the crystal structure. The results showed that amphibole in the SYS is mainly magnesiohornblende (52.2% 81.4%) in the calcic amphibole subgroup, followed by tschermakite.The source rock types of amphibole are mainly different types of magmatic (ultrabasic, basic, and  Corresponding author.